(untitled) (Web of Technology: Multidimensional Research Journal, 2025)
The article presents the results of research on the development of a technology for increasing the flame resistance of cellulose-based fabrics by treating them with modified aerosil-380 nanoparticles. Based on the results of the conducted research, a full-cycle technology was developed.